The role of government auditing in controlling the level of corruption in Indonesia - Anggreni Dian Kurniawati; Yohanes Mario Pratama (Jurnal Akuntansi dan Auditing Indonesia, 2021)
The regional autonomy system has a great impact on the Indonesian local government to create good governance so as to prevent corruption. This study aims to examine the impact of detection of irregularities, audit opinion, and audit rectification on the level of corruption in provincial governments in Indonesia. The data collected in this research was the audit report of the Audit Board of the Republic of Indonesia and the annual report of The Corruption Eradication Commission in 34 provinces in 2015-2019. Further, the data was analyzed using multiple linear regression. The results indicate that the detection of irregularities and audit rectification has a positive impact on the level of corruption, while the irregularities and audit opinion do not have impact on the level of corruption. These results are expected to encourage the government to strengthen its financial supervision system.